Proverbs 31:10-31 from a Ghanaian and (Akan) womanist perspectives- Inculturation and Liberation Hermeneutics approach - Human, Dirk J. (University of Pretoria, 2024)
Thesis (PhD (Old Testament studies))--University of Pretoria, 2023.